2019
DOI: 10.1183/13993003.01523-2018
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of cathepsin S reduces cystic fibrosis-like lung disease

Abstract: Cathepsin S (CatS) is upregulated in the lungs of patients with cystic fibrosis (CF). However, its role in CF lung disease pathogenesis remains unclear.In this study, β-epithelial Na+ channel-overexpressing transgenic (βENaC-Tg) mice, a model of CF-like lung disease, were crossed with CatS null (CatS−/−) mice or treated with the CatS inhibitor VBY-999.Levels of active CatS were elevated in the lungs of βENaC-Tg mice compared with wild-type (WT) littermates. CatS−/−βENaC-Tg mice exhibited decreased pulmonary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 41 publications
3
47
0
Order By: Relevance
“…CTSS is emerging as an important player in early CF lung disease with extracellular CTSS levels correlating significantly with lung function decline and neutrophil recruitment into the airways (47). A recent study, using the βENaC-overexpressing mouse with CF-like lung disease, elucidated roles for CTSS in the in vivo pathogenesis of several key CF pathologies (48). In this study, genetic and pharmacological knockdown of CTSS was associated with a reduction in neutrophil recruitment and amelioration of airway mucus obstruction and lung tissue destruction.…”
Section: The Actions Of Cysteine Proteases In Cfmentioning
confidence: 99%
See 2 more Smart Citations
“…CTSS is emerging as an important player in early CF lung disease with extracellular CTSS levels correlating significantly with lung function decline and neutrophil recruitment into the airways (47). A recent study, using the βENaC-overexpressing mouse with CF-like lung disease, elucidated roles for CTSS in the in vivo pathogenesis of several key CF pathologies (48). In this study, genetic and pharmacological knockdown of CTSS was associated with a reduction in neutrophil recruitment and amelioration of airway mucus obstruction and lung tissue destruction.…”
Section: The Actions Of Cysteine Proteases In Cfmentioning
confidence: 99%
“…Matrix degradation Serine, cysteine, MMP (52,54,55,70) Cytokine processing Serine, cysteine, MMP (14,18,46,56) Cytokine upregulation Serine, cysteine, MMP (15,48,54,55) PAR activation Serine, cysteine, MMP (48,71) Trans-class protease activation Serine, cysteine (9,12,26,27) Host defence protein degradation (including antiproteases)…”
Section: Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we show that lack of IL-1R reduced emphysema-like lung damage, as determined from measurements of MLI and DI in juvenile Scnn1b-Tg/Il1r1 -/mice ( Figure 5A-C). In previous studies we demonstrated that neutrophil elastase (NE), macrophage elastase (matrix metalloproteinase 12 ) and cathepsin S released from activated neutrophils and macrophages in mucostatic airways, are major contributors to structural lung damage in Scnn1b-Tg mice (28,35,36). While airway neutrophils were also reduced in Scnn1b-Tg/Il1r1 -/mice ( Figure 1C), it is important to note that Scnn1b-Tg/NE -/presented with residual emphysema suggesting that other factors may contribute to emphysema formation in this model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, instillation of CatS into the lungs of wild-type mice results in inflammation, lung remodelling, and upregulation of mucin expression, while CatS inhibition leads to a reduction in airway inflammation and mucin expression. Taken together, it has been proposed that CatS plays a critical role in the pathogenesis of cystic fibrosis and some CF-like lung diseases, highlighting CatS as a valuable therapeutic target [57]. Nevertheless, cathepsins B, H, K, L, and S levels remain unchanged in the sputum of CF patients infected or not by Pseudomonas aeruginosa, suggesting that they are not markers of bacterial infection [58].…”
Section: Cysteine Cathepsins In Pulmonary Diseasesmentioning
confidence: 99%